PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP KECENDERUNGAN POLA HIDUP MAHASISWA PASCASARJANA UNIVERSITAS NEGERI MAKASSAR PRODI IPS DI ERA DIGITAL - Astria Wulandari; Nur Fadhilah Murtadir; Alfian Dahrun; Sahrah Fadillah Usman; Romansyah Sahabuddin; Agus Salim; Naja Muddin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2026)
This study aims to analyze the influence of Instagram social media usage on the lifestyle tendencies of postgraduate students of Makassar State University, Social Sciences Study Program in the digital era. This study uses a quantitative approach with a simple linear regression design. The research sample consisted of 45 students selected through purposive sampling technique. Data collection was conducted using a Likert scale questionnaire that has been tested for validity and reliability. The results show that Instagram usage has a significant effect on the lifestyle tendencies of students, indicated by a significance value <0.001 and a positive regression coefficient of 0.766. The R² value of 0.252 indicates that 25.2% of lifestyle pattern variations are explained by Instagram usage. This study concludes that the intensity of Instagram usage contributes to the lifestyle tendencies of students, so that strengthening digital literacy is needed to direct the use of social media more productively.